Determinants of Environmental Conflict: When Do Communities Mobilize against Fossil Fuel Production?. (August 2021) - Cheon, Andrew; Kang, Shi-Teng; Ramachandran, Swetha
When do indigenous and other negatively affected populations mobilize against fossil fuel companies? We revisit social movement theory and environmental literature to identify three factors that may plausibly shape mobilization decisions of negatively affected populations—democratic institutions, community perceptions of government shaped by land tenure security, and firm attributes. Democratic institutions afford more opportunities for affected populations to air their grievances through protests than non-democratic ones. Land tenure security guaranteed by government contributes to the perception among affected populations that their objectives are better achieved through government mediation than protests. Characteristics of fossil fuel firms, such as state ownership, also shape activist perceptions of government credibility as a mediator. By analyzing fifty-seven countries over the period 1990 to 2013, we find that democracy and state ownership of fossil fuel firms are positively associated with protests, whereas land tenure security is negatively associated.